The Impact of Reading Instructional Time in the Classroom - Atique ur Rehman (Universidade de Lisboa, 2021)
Reading is without doubt a highly complex cognitive process and hence it is a difficult task to formulate policies for its' improvement. An effective reading time allocation is particularly important for the improvement of early grade reading. DeStefano (2012) illustrated that with all things being equal, students who spend more class time on a learning task perform better than students who spend less time. It has been seen that children come to school with little to no reading skills in the language of instruction, which puts them at a further disadvantage. Students who do not achieve a certain level of reading by the end of grade 1 tend to fall behind in all other areas of cognitive development (Stanovich, 1986). This study would explore the reading instruction time policy initiative and discuss how it developed and ensured in the early grades classes in Pakistan. This is a mixed-methods approach study that combines both qualitative and quantitative data. The study showed elements that contributed to improve early grades reading skills, especially help the number of students' zero scores decreased in reading tasks and support the education departments to achieve the performance standards.